Domenico Losurdo in Cina: uno sguardo sulla situazione della formazione marxista e del PCC - Boer, Roland (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2021)
This study draws on an experience of leading a seminar series in China on the work of the Italian Marxist philosopher, Domenico Losurdo. Through this seminar series and the extensive engagements with the seminar participants – all members of the CPC and teachers of Marxism – I have been able to gain a unique insight into the state of Marxist education and indeed of theoretical knowledge in the CPC itself. The emphases were on Losurdo’s two books translated into Chinese, one on liberalism and other on Hegel. We focused on issues of relevance to China today. In regard to liberalism, the topics were: the paradox of liberalism in terms of its constitutive unfreedom; class consciousness; and how liberalism attempts to manage its internal contradiction. As for Hegel, these concerned: the state; material rights; and revolution. While the topics themselves and the way they are presented reflect discussions in the seminars and indicate distinct Chinese concerns, the conclusion assesses the current status of Marxism in education and the CPC. Losurdo; Marxism in China; Liberalism; Hegel.